FEATURES OF THE COURSE OF RENAL DYSFUNCTION (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The article presents the results of a comparative analysis of clinical manifestations and hemodynamic parameters in 80 patients with renal dysfunction and 80 patients with arterial hypertension without signs of renal dysfunction. It was shown that disturbances in water–salt metabolism, нарушения циркадного ритма, and increased activity of the renin–angiotensin–aldosterone system lead to more pronounced clinical and hemodynamic changes in patients with renal dysfunction.
Keywords: Blood pressure, arterial hypertension, renal dysfunction, circadian index, clinical manifestations.